(untitled) (Annals of Medical Research, 2021)
Aim: Diabetic dermopathy is a skin disease, seen in patients with diabetes mellitus, characterized by atrophic scar and hyper-pigmented lesions. Recently, it was proposed that this disease might be associated with other microangiopathic complications of diabetes such as retinopathy, nephropathy, and polyneuropathy. In this study, patients with diabetic dermopathy were compared with two control groups to test the validity of these associations.Material and Methods: Twenty-three patients, who admitted to Dermatology Outpatient Clinic Health Sciences University Gazi Yaşargil Education and Research Hospital and diagnosed as diabetic dermopathy were included in the study. Twenty-three patients with well controlled diabetes mellitus (Control Group A) who treated as outpatients and 23 patients with diabetes mellitus who had poor general status and hospitalized by internal medicine department (Control Group B) were included as two control groups. Patients were evaluated in terms of retinopathy, nephropathy, neuropathy, heart attack history and diabetic foot ulcer.Results: In the study 82.6% (n:19) of patients were male and 17.4% (n:4) were female (female: male ratio 4.75:1). There was no significant relationship between fasting blood glucose and HbA1c elevation with retinopathy, neuropathy, polyneuropathy and diabetic foot. However, there was a significant relationship between fasting blood glucose levels and heart attack. Although heart attack history and diabetic foot was more common in the patient group and retinopathy, nephropathy and polyneuropathy was more frequent in the Control Group B, there was no significant difference between both groups.Conclusions: In conclusion, microangiopathic complications, heart attack and diabetic foot are not only common in the patient group with diabetic dermopathy but also in the Control Group B. Even though these complications were more common in these two groups, there was no significant difference between each and the other diabetic (Control Group A).Keywords: Diabetes mellitus; diabetic dermopathy; skin lesions; cutaneous manifestations.